Choosing the Best House in a Bad Neighborhood: Location Strategies of Human Rights INGOs in the Non‐Western World1. Issue 1 (15th December 2014) - Barry, Colin M.; Bell, Sam R.; Clay, K. Chad; Flynn, Michael E.; Murdie, Amanda
<x xml:space="preserve">Abstract</x> What determines the location of those human rights international non‐governmental organization (INGO) resources found outside of the highly developed Western democracies? We draw a distinction between the bottom‐up mobilization processes driving the location of human rights organization (HRO) members from the top‐down strategic concerns driving where HRO leaders place permanent offices. In particular, we find that, while political opportunity structures generally increase the likelihood that a state has HRO members, it has a curvilinear influence on the number of HRO secretariats, which typically locate in areas seen as having a higher need for organizational resources. Further, while there is no clear connection between human rights abuses and HRO memberships in a state, HROs' strategic concerns lead them to place offices with reference to both local and neighborhood "need"—in other words, levels of repression.